Olam extends ambition to reduce Food, Loss and Waste (FLW), and Greenhouse Gas (GHG) emissions to 9 crops next to rice - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Based on learnings in rice case study, Olam wants to extend the approach to their main other crops. They post a call for proposals for a generic ACE calculator methodology.